Mineral carbonation of serpentinite: From the Laboratory to Pilot Scale - The MCi project - Brent, G.; Rayson, M.; Kennedy, E.; Stockenhuber, M.; Collins, Bill; Prigge, J.; Hynes, R.; Molloy, T.; Zulfiqar, H.; Farhang, F.; Oliver, T.; Hamblin Wang, S.; et al. (2015)
To date, ex-situ carbonation of ultramafic ores such as serpentinite has been studied extensively on the laboratory scale. In Australia, the Mineral Carbonation International (MCi) project was launched in 2013, with funding from the New South Wales (NSW) State and the Australian Federal Governments as well as an industry partner, Orica. The project aims to demonstrate the techno-economic viability of mineral carbonation as a sustainable industrial solution for carbon capture, storage and utilisation (CCSU). For the first time, mineral carbonation of silicate ore will be studied at a scale several orders of magnitude greater than laboratory scales hitherto. The MCi project is believed to be the first holistic approach to CCSU via mineral carbonation, examining the full chain of operations from feedstock to final product. It comprises three core themes; the construction and operation of a research pilot plant, a portfolio of research projects and support activities and commercialisation. The research encompasses mineral mapping, characterisation, processing and pretreatment through to process integration with power generation and CO 2 capture, fundamentals of carbonation chemistry, value-adding and final product storage. In line with this holistic approach, Life Cycle Assessments (LCAs) are being conducted.